ANALYSIS OF THE APPLICATION OF PATIENT SAFETY (Case Study at Ratu Aji Putri Hospital Botung Penajam Paser Utara 2016-2021 - Syahrial Hidayat; Farida Yuliaty; Etty Sofia (Sean Institute, 2023)
To prevent nosocomial infections, it is necessary to implement patient safety. Patient safety is a condition of being safe physically, socially, spiritually, financially, politically, emotionally, occupationally, psychologically and avoiding various threats. This study aims to analyze the application of patient safety at Ratu Aji Putri Hospital Botung Penajam Paser Utara. The research method used was a case study with a qualitative approach where the informants were the hospital director, the patient safety team leader, the head of the nurse's room and the patient. Methods of collecting and processing data with observational participants, independent interviews and triangulation. Based on the results of the study, it shows that the leadership behavior of the head of the room is directive, where there are obstacles in its implementation that have not been carried out optimally due to a reporting gap that has not been carried out by the head of the room with the management. The communication made by the head of the room with the nurses has been going well but the management has never received positive feedback and there is no freedom and limited expression of opinions or policy proposals. Coordination and division of tasks have been carried out properly, fairly and evenly. Management pays more attention to completing and seeking officers to actively express opinions, it is hoped that this will develop patient safety training programs for officers.